Mekanisme Penambatan Nitrogen Udara oleh Bakteri Rhizobium Menginspirasi Perkembangan Teknologi Pemupukan Organik yang Ramah Lingkungan - GEDE MENAKA ADNYANA (Agrotrop : Journal on Agriculture Science, 2012)
Interaction of microbes with human living in the nature are able to seen from their capabilitiesimproving the environmental by composting waste of agriculture to become organic fertilizer. In thecontrary, the epidemic and infectious phatogens are also its contribution. In agriculture sector, the livingof microbes has been explored to keep the soil fertile, and to improve growth and plant production.The symbiosis of Rhizobium bacteria with the specific host plant from legumes is able to run because ofboth side giving a signal, where host plant give an organic molecoles called inducer. From the bacteriaside, also give an organic materials called nod factor. The step of nitrogen fixation mechanism can bedescribed from infection of root legume as the first step, followed by the nitrogen fixation by thebacteroid and synthesis of the nitrogen organic by host plant as the last step. These natural processesinspire finding and development of the ecologically organic fertilizer technology.